Sharing Prosperity: Distributive Justice Framework in An Islamic Moral Economy - Furqani, Hafas; Mulyany, Ratna (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
The issue of distribution in an Islamic economy is not about the allocation of resources/output per se. It is about a ‘just’ allocation of resources/output. This article attempts to elaborate Islamic concept of distribution by exploring the goals of distribution in Islamic economics and mechanisms to achieve distributive justice goals. The focus of discussion is about how to realize ‘distributive justice’ in an Islamic moral economic framework by considering all dimensions: right and responsibility, effort and surplus of individual and public interest. In that spirit, the policy for distributive justice in an Islamic moral economy aims to achieve certain objectives, namely (1) fulfilment of basic needs, (2) establishing socio-economic justice and (3) economic empowerment. To achieve those objectives, Islam uses both moral exhortation to encourage voluntary action and rules/legal measures to ensure distribution/allocation of wealth in society. The distribution scheme in an Islamic economy would attempt to eliminate poverty and deprivation so that the basic needs of all are duly fulfilled. In practice, Islamic economics distribution system is done through (1) the establishment of initial conditions in distribution as the basis upon which operational distribution should be taken place during production and after production; (2) distribution through factor payment; and (3) distribution through transfer payment in the form of compulsory transfers, voluntary transfers and transfer through state. Permasalahan distribusi dalam ekonomi Islam bukan hanya tentang alokasi sumber daya / output, namun lebih tentang alokasi sumber daya secara 'adil'. Artikel ini mencoba untuk menguraikan konsep distribusi Islam dengan mengeksplorasi tujuan distribusi dalam ekonomi Islam dan mekanisme untuk mencapai tujuan keadilan distributif. Fokus kajiannya adalah bagaimana mewujudkan 'keadilan distributif' dengan mempertimbangkan semua dimensi seperti hak dan tanggung jawab, upaya dan surplus kekayaan individu dan publik. Kebijakan keadilan distributif dalam ekonomi Islam bertujuan untuk mencapai tujuan: (1) pemenuhan kebutuhan dasar, (2) membangun keadilan sosial-ekonomi dan (3) pemberdayaan ekonomi. Untuk mencapai tujuan-tujuan tersebut, Islam menggunakan nasihat moral untuk mendorong tindakan sukarela dan juga aturan/tindakan hukum untuk memastikan distribusi/alokasi kekayaan dalam masyarakat. Skema distribusi dalam ekonomi Islam ditujukan untuk menghilangkan kemiskinan dan ketimpangan sehingga kebutuhan dasar semua terpenuhi. Dalam praktiknya, sistem distribusi ekonomi Islam dilakukan melalui (1) penetapan kondisi awal dalam distribusi sebagai dasar di mana distribusi operasional harus dilakukan selama produksi dan setelah produksi; (2) distribusi melalui pembayaran faktor; dan (3) distribusi melalui pembayaran transfer dalam bentuk transfer wajib, transfer sukarela dan transfer melalui negara.